2017
DOI: 10.1098/rsos.170480
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of trace metal uptake in cells by inulin coating of metallic nanoparticles

Abstract: Trace elements such as zinc and iron are essential for the proper function of biochemical processes, and their uptake and bioavailability are dependent on their chemical form. Supplementation of trace metals through nanostructured materials is a new field, but its application raises concerns regarding their toxicity. Here, we compared the intracellular zinc uptake of different sources of zinc: zinc sulfate, and ZnO and core-shell α-Fe2O3@ZnO nanoparticles, coated or uncoated with inulin, an edible and biocompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…Exposure to soluble copper has also been reported to decrease phagocytic activity of clam hemocytes . This effect of decreased phagocytic activity of mussel hemocytes has been reported for in‐vitro exposure to nCuO, where other negative effects were observed, such as a decreased cell viability . Here, we observed that in‐vivo exposure of mussels to either source of copper to nCuO caused a significant increase in lysosome abundance and ROS production, and a decreased MDR activity in hemocytes.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Exposure to soluble copper has also been reported to decrease phagocytic activity of clam hemocytes . This effect of decreased phagocytic activity of mussel hemocytes has been reported for in‐vitro exposure to nCuO, where other negative effects were observed, such as a decreased cell viability . Here, we observed that in‐vivo exposure of mussels to either source of copper to nCuO caused a significant increase in lysosome abundance and ROS production, and a decreased MDR activity in hemocytes.…”
Section: Discussionsupporting
confidence: 83%
“…Phagocytosis assays were performed in 24‐well plates as previously reported . Briefly, approximately 500 000 fluorescently labeled yeast suspended in 500 μL of physiological saline (PS, 20 mM HEPES, 436 mM NaCl, 10 mM KCl, 53 mM MgSO 4 and 10 mM CaCl 2 , pH 7.3) were added to each well containing approximately 50,000 hemocytes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[48][49][50][51][52][53] Most recently our research has focused on exploring alternative biocompatible polymeric coatings for these nanoparticles. 54,55 Here, the preparation and characterization of CMC coated magnetite nanoparticles (Fe 3 -O 4 @CMC) and the evaluation of their performance as drug delivery systems for dopamine are presented. Fluorescence and electron microscopy (SEM and TEM) studies were used to analyze the cell viability of HLMVE cell cultures exposed to the magnetic nanoparticles and their interaction with cell components.…”
Section: Introductionmentioning
confidence: 99%